ESCALATING VOCABULARY MASTERY: HOW EFFECTIVE IS SPOTIFY"™S SONG LIRYCS FEATURE? - Rasyida, Jihan; Izzah, Lidiyatul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aimed: 1) to compare vocabulary mastery of experimental and controlled groups students after the treatment, 2) to see the difference gained by the two groups in terms of their vocabulary achievement, and 3) to measure how effective song lyrics feature was, available on Spotify, in the development of students"™ vocabulary mastery. There were two classes of 8th graders of Jagakarsa junior high school, Jakarta participated as the sample in this study, classified into experimental and controlled groups.  A total number of 28 students occupied each of the class. The data were collected by using 30 multiple-choice questions of vocabulary pre- and post-tests. This research applied quantitative method. Thus, in the analysis data, statistical formula of t-test and effect size tests were used. The results of the computation revealed: 1) in the average, experimental group students outperformed controlled group ones in which these students"™ vocabulary achievement escalated up to 22.04 points while the controlled group only increased 9.64 points; 2) The statistical analysis of t-test confirmed that t0 t-table and the value of Sig. (2-tailed) 0.05. Thus, these indicated that there was no difference in the average score achieved by experimental and controlled classes, hence, H0 was accepted. 3) In terms of its effectiveness, the used of songs"™ lyrics on Spotify as teaching and learning media was not contributed fully towards students"™ vocabulary mastery; this was showed by the value of 0.518 (moderate level) from the effect size test. This research work concluded that songs"™ lyrics on Spotify was not really effective in improving students"™ vocabulary mastery.